Limnology of Macrobrachium amazonicum grow-out ponds subject to high inflow of nutrient-rich water and different stocking and harvest management - Kimpara, Janaina Mitsue; Tito Rosa, Fabricio Ribeiro [UNESP]; Preto, Bruno de Lima [UNESP]; Valenti, Wagner Cotroni [UNESP] (Wiley-Blackwell, 2011)
We evaluated the water characteristics and particle sedimentation in Macrobrachium amazonicum (Heller 1862) grow-out ponds supplied with a high inflow of nutrient-rich water. Prawns were subject to different stocking and harvesting strategies: upper-graded juveniles, lower-graded juveniles, non-graded juveniles + selective harvesting and traditional farming (non-grading juveniles and total harvest only). Dissolved oxygen, afternoon N-ammonia and N-nitrate and soluble orthophosphate were lower in the ponds in comparison with inflow water through the rearing cycle. Ponds stocked with the upper population fraction of graded prawns showed higher turbidity, total suspended solids and total Kjeldahl nitrogen than the remaining treatments. An increase in the chemical oxygen demand:biochemical oxygen demand ratio from inlet (4.9) to pond (7.1-8.0) waters indicated a non-readily biodegradable fraction enhancement in ponds. The sedimentation mean rate ranged from 0.08 to 0.16 mm day(-1) and sediment contained >80% of organic matter. The major factors affecting pond ecosystem dynamic were the organic load (due to primary production and feed addition) and bioturbation caused by stocking larger animals. Data suggest that M. amazonicum grow-out in ponds subjected to a high inflow of nutrient-rich water produce changes in the water properties, huge accumulation of organic sediment at the pond bottom and non-readily biodegradable material in the water column. However, the water quality remains suitable for aquaculture purposes. Therefore, nutrient-rich waters, when available, may represent a source of unpaid nutrients, which may be incorporated into economically valued biomass if managed properly.
Keywords: Macrobrachium; nutrient-rich water; selective harvesting; juveniles grading; water quality; sedimentation